2020
DOI: 10.1371/journal.pone.0231847
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four sarcopenia screening questionnaires in community-dwelling older adults from Poland using six sets of international diagnostic criteria of sarcopenia

Abstract: Introduction There are four screening sarcopenia questionnaires (SARC-F, SARC-CalF, MSRA-5, MSRA-7). To unambiguously determine which of them is the most effective tool in community-dwelling older adults, we performed a diagnostic accuracy study. The aim of the analysis was to assess the diagnostic values of SARC-F, SARC-CalF, MSRA-5, MSRA-7 and compare their psychometric properties against six criterion standards (EWGSOP1, EWG-SOP2, FNIH, AWGS, IWGS, SCWD criteria). Materials and methods We included 100 commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
2
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 37 publications
1
30
2
4
Order By: Relevance
“…The best combination of sensitivity and specificity values for sarcopenia diagnosis in our population of hospitalized subjects was obtained at 22.5 points, corresponding to a score lower than 25 in the 7-item MSRA, and at 37.5 points, corresponding to a score lower than 40 in the 5-item MSRA. This is in line with the results of Kryinska-Siemaszko et al, who showed that the MSRA questionnaire, also exploring nutritional deficiencies and their role in sarcopenia development, requires a lower cut-off for both the 7-and 5-items when applied to a population of subjects with high prevalence of malnutrition [24].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The best combination of sensitivity and specificity values for sarcopenia diagnosis in our population of hospitalized subjects was obtained at 22.5 points, corresponding to a score lower than 25 in the 7-item MSRA, and at 37.5 points, corresponding to a score lower than 40 in the 5-item MSRA. This is in line with the results of Kryinska-Siemaszko et al, who showed that the MSRA questionnaire, also exploring nutritional deficiencies and their role in sarcopenia development, requires a lower cut-off for both the 7-and 5-items when applied to a population of subjects with high prevalence of malnutrition [24].…”
Section: Discussionsupporting
confidence: 89%
“…To the best of our knowledge, only few studies have evaluated the reliability of sarcopenia questionnaires in an acute care ward and no previous studies have tested the predictive value of the combination of both questionnaires [ 23 , 24 , 25 ]. The best combination of sensitivity and specificity values for sarcopenia diagnosis in our population of hospitalized subjects was obtained at 22.5 points, corresponding to a score lower than 25 in the 7-item MSRA, and at 37.5 points, corresponding to a score lower than 40 in the 5-item MSRA.…”
Section: Discussionmentioning
confidence: 99%
“…community health care and other clinical settings. 11,65 With its low sensitivity but high specificity, the SARC-F will most likely detect severe cases rather than low-risk patients. 66,67 To increase its sensitivity, Barbosa-Silva et al 68 added calf circumference to the SARC-F questionnaire, resulting in the SARC-CalF screening tool.…”
Section: Dovepressmentioning
confidence: 99%
“…A recent comparative study found that the SARC-CalF was the optimal choice for screening sarcopenia in community dwelling-older adults. 65 Following this recent literature, the AWGS 2019 recommends the use of the SARC-CalF in their screening protocol. 12 • Recently the serum creatinine (Cr)/serum cystatin C (CysC) ratio, also called the sarcopenia index, has been introduced.…”
Section: Dovepressmentioning
confidence: 99%
“…However, these screening tools provided contradictory results in many cases due to their scarce sensitivity but high specificity (in other words, only severe cases may be detected with a high rate of false negatives). Nevertheless, their predictive values in diagnosing sarcopenia are generally acceptable, especially for primary prevention [112,113]. Unfortunately, there is relatively limited evidence from experimental studies of their effectiveness and it is unclear which of these current tools is the most effective in screening for sarcopenia in the community.…”
Section: Now Is the Time To Screen For Sarcopeniamentioning
confidence: 99%